Multilingual language assistants, investment and social justice in second language learning for adult newcomers - Eek, Marianne (Studies in the education of adults, 2025)
This article investigates the significance of the use of multilingual language assistants (MLAs) in second language teaching for adult migrants with limited formal schooling. Norton’s theories of investmentand critical pedagogy serve as an analytical backdrop. An emic perspective is adopted, with interviews with nine adult learners taking centre stage. The data also includes interviews with three teachers, as well as classroom observations. Analysis of the learner interviews points to the importance of the MLAs when it comes to meeting the adult newcomers’ basic needs for security, understanding and recognition. The data as a whole suggests that MLAs contribute to the language learners participating more actively in the learning process. The analysis provides insight into possibilities and limitations for second language learning, related to the subject positions available in the classroom, whether or not their linguistic capital is recognised and their access to new linguistic capital, and the different language ideologies at play. The purpose of the article is to encourage reflections on learning conditions for adult newcomers with limited formal schooling.